Origin of the left coronary artery from the right pulmonary artery and ventricular septal defect in a child of a mother with raised plasma phenylalanine concentrations throughout pregnancy. Issue 3 (March 1990) - Henglein, D; Niederhoff, H; Bode, H
Abstract : A child with anomalous origin of the left coronary artery from the right pulmonary artery, ventricular septal defect, fetal growth retardation, and facial abnormalities was born to a woman in whom plasma phenylalanine concentrations had been raised throughout pregnancy. The cardiac abnormalities were diagnosed by angiography when the child was eight months old. The anomalous coronary artery was imaged in a subsequent echocardiogram. Development retardation was caused by maternal phenylketonuria, which may also have been responsible for the development of the ventricular septal defect and the coronary anomaly. If dietary treatment of the mother had been started before pregnancy damage to the child might have been prevented.